PENGEMBANGAN MEDIA PEMBELAJARAN E-COMIC BERBASIS ETNOMATEMATIKA WAYANG KULIT UNTUK MENUNJANG KEMAMPUAN LITERASI NUMERASI - Aleza Dwi Septi; Wiwin Astuti; Heldy Ramadhan Putra P; Lila Pangestu Hadiningrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low level of students' numeracy literacy and the limited variety of media in mathematics learning are the background for this research. The purpose of this research is to describe the development process and determine the level of feasibility and practicality of the developed media. The main focus is to develop e-comic learning media that facilitates the understanding of the concept of congruence while supporting numeracy literacy skills through an ethnomathematics approach. The research procedure applies the Research and Development development method with a 4D model limited to the Define, Design, and Development stages. This media development was carried out by identifying congruent shapes in the shadow puppet characters Wijanarka, Werkudara, Baladewa, and Semar, then arranged using the Canva application in flipbook format. The validation results showed a feasibility level of 88.93% from material experts and 90% from media experts, both of which are included in the